Pengelolaan Hipertensi Dengan Terapi Mudra Sujok : Studi Kasus - Agus Setyo Utomo; Lucia Retnowati; Rahul Nurcholik (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2026)
Hypertension remains a major global health problem with a high prevalence in Indonesia and requires long-term management. Although pharmacological therapy is effective, patient adherence is often suboptimal due to concerns about long-term side effects, highlighting the need for safe, simple, and self-managed non-pharmacological alternatives. This study aimed to evaluate the effectiveness of Mudra Sujok therapy as a tool-free non-pharmacological intervention in hypertension management, focusing on blood pressure reduction, sleep quality improvement, and patient adherence. An observational case study design was employed involving two hypertensive patients who performed Mudra Sujok therapy independently for 14 days at Pandanwangi Primary Health Center, Malang City. Data were collected through interviews, blood pressure measurements, and sleep quality assessments. The results demonstrated reductions in both systolic and diastolic blood pressure, improved sleep quality, and high levels of adherence to the therapy among both subjects. The novelty of this study lies in the application of Mudra Sujok as a single, tool-free Sujok method that is simple, safe, and easily replicated, thereby supporting patient self-management and family involvement in hypertension care. Mudra Sujok therapy can be performed independently with family support, such as reminding therapy schedules, creating a relaxing home environment, and encouraging adherence to non-pharmacological hypertension management. These findings contribute to the development of a more holistic hypertension management model in primary healthcare settings. Further studies with larger sample sizes and experimental designs are recommended to confirm the long-term effects of Mudra Sujok therapy.